Rural Life in "Adventures of Huckleberry Finn" by Mark Twain - Nadia Hulwa; Ferdinal Ferdinal (Vivid: Journal of Language and Literature, 2022)
This research studies rural life as the setting in Mark Twain’s masterpiece, Adventures of Huckleberry Finn. This research investigates rural life employed by Mark Twain as the setting in the novel. Besides, it highlights the kinds of rural settings intertwined in the story. Finally, this research also investigates how far the settings function to deliver the theme of the novel. In analyzing the work, the study applies a formalist approach that focuses on the text’s intrinsic elements, in this case, the settings. It also utilizes the qualitative method and library research as the method of the study. Finally, it is found that the settings of place are the most dominant setting that carries the novel’s rural aspect compared to the time and social settings. Mississippi River and the villages as the settings of place also play an essential role in delivering one of the story’s themes, the conflict between natural life and civilized life.